Effects of Aging on the Color and Translucency of Monolithic Translucent Y-TZP Ceramics: A Systematic Review and Meta-Analysis of In Vitro Studies. (27th January 2021) - Zhang, Chang-yuan; Agingu, Check; Tsoi, James Kit Hon; Yu, Hao
Abstract : Background . Monolithic restorations made of translucent yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) have become popular over the past few decades. However, whether aging affects the color and translucency of monolithic translucent Y-TZP is unclear. Objective . The aim of this systematic review and meta-analysis of in vitro studies was to evaluate the effects of aging on the color and translucency of monolithic translucent Y-TZP ceramics. Materials and Methods . This systematic review/meta-analysis was reported according to the PRISMA statement and registered in the OSF registries (https://osf.io/5qjmu ). Four databases including Medline via the PubMed, Embase, and Web of Science databases and the Cochrane Library were searched using no publication year and language limits. The last search was executed on November 20, 2020. In vitro studies comparing the translucency and/or color of monolithic translucent Y-TZP ceramics before and after simulated aging were selected. Meta-analyses were performed using Review Manager software (version 5.3, Cochrane Collaboration, Oxford, UK) with random-effects models at a significance level of 0.05. A risk-of-bias assessment was also performed for the included studies. Results . Of the 188 potentially relevant studies, 13 were included in the systematic review. The hydrothermal aging duration ranged from 1 to 100 h at relatively similar temperatures (~134°C). In the general meta-analyses, the aged Y-TZP ceramics exhibited similar translucency parameter (TP), L ∗, and b ∗ values compared with the nonaged controls (P = .73, P = .49, and P = .62, respectively). Moreover, there was a significant difference between the aged and nonaged Y-TZP ceramics in the a ∗ value (P = .03 ; MD = − 0.26 ; 95% CI = − 0.51   to − 0.02 ), favoring the nonaged Y-TZP ceramics. The subgroup analyses showed that the duration of aging contributed to changes in the translucency and color of the Y-TZP ceramics. Conclusions . The optical properties of monolithic translucent Y-TZP ceramics were stable after hydrothermal aging at 134°C and 0.2 MPa for ≤20 h. Moreover, clinically unacceptable changes in the translucency and color of monolithic translucent Y-TZP ceramics were found after hydrothermal aging for >20 h.